The Relationship Between Perception of Environmental Knowledge and Practices Among Upper Secondary Vocational Program Students in Batu Pahat District - Mohd Sabran, Farhana; Abdullah, Nurul Hidayah Liew (Online Journal for TVET Practitioners, 2025)
Environmental education plays a crucial role in raising awareness and fostering environmental responsibility, particularly among students. However, the level of environmental knowledge and practices among Malaysian students remains a concern. This study aims to examine the relationship between students' perceptions of environmental knowledge and their environmental practices. A quantitative survey design was employed, involving 92 Upper Secondary Vocational Program (PVMA) students from four schools in Batu Pahat District. Data were analyzed using descriptive statistics, including mean and standard deviation, as well as Pearson correlation analysis. The findings indicate that while students exhibit a high level of perceived environmental knowledge, their environmental practices remain at a moderate level. Additionally, no significant relationship was found between students' perceptions of environmental knowledge and their actual environmental practices. These results suggest that possessing environmental knowledge does not necessarily translate into proactive environmental behaviour. In conclusion, strengthening environmental education through practical engagement is essential to bridging this gap. The findings of this study can serve as a valuable reference for future research aimed at enhancing environmental practices among students.